Maturity Level Measurement Model of MSMEs for Sustainable Economic Growth - Lukita, Chandra; Chandra, Aditya Kurniawan; Fahrudin, Rifqi; Agatha, Niken Maria; Suci, Dina Perme (Aptisi Transactions On Technopreneurship (ATT), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in regional economic development, particularly in the culinary sector. However, culinary MSMEs in secondary urban areas such as Cirebon City face persistent challenges in adapting to digital transformation, including limited digital literacy, weak financial management, and low integration with digital business ecosystems. The absence of a contextual and measurable framework to assess digital readiness further constrains strategic decision-making and long-term competitiveness. This study aims to develop a digital maturity measurement model for culinary MSMEs in Cirebon City to systematically evaluate their level of digital readiness and support sustainable economic growth. A mixed-method research design was applied using a sequential explanatory approach. Quantitative data were collected through Likert-scale questionnaires distributed to 150 culinary MSMEs, measuring three core dimensions: Financial Health, Market Capitalization, and Local Digital Mapping. Instrument reliability was confirmed using Cronbach’s Alpha. Qualitative data were obtained through in-depth interviews and field observations to validate and contextualize the quantitative findings. The findings reveal that approximately 65% of MSMEs remain at the Survival stage, characterized by minimal adoption of digital accounting, digital marketing, and e-commerce platforms. Financial Health emerged as the weakest dimension, followed by Market Capitalization. Based on empirical evidence, MSMEs were classified into three maturity stages: Survival, Momentum, and Expansion. The proposed model offers a valid and practical tool for MSMEs and policymakers to assess digital maturity and design targeted empowerment strategies. This study contributes to the literature on MSME digital transformation and supports the achievement of SDG 8 and SDG 9.